Investigation on high-temperature creep behavior at 300 °C in laser-welded joints of a novel heat-resistant Al alloy of Al–12Ce-0.4Sc - Jie Ning; Chao Feng; Linjie Zhang (Journal of Materials Research and Technology)
The scarcity of studies on the high-temperature creep behavior of laser welds in heat-resistant Al alloys limits their widespread application. This study examines the effects of laser welding and heat treatment on the high-temperature creep performance of the Al–12Ce-0.4Sc alloy at 300 °C. The joint subjected to post-heat treatment demonstrated superior high-temperature creep properties at 300 °C, with no fractures occurring after 100 h of creep at 55 MPa. The steady-state creep rate was approximately 9 × 10−9 s−1. The disappearance of primary Al11Ce3 in the weld area, coupled with a significant reduction in grain size and the presence of cellular eutectic Al11Ce3, are the primary factors contributing to its superior resistance to high-temperature creep compared to the base material. The Schmid factor for the [111] ⟨11‾0⟩ slip system and the changes in dislocation density before and after creep were analyzed. The proportion of soft orientation in the Schmid factor for the base material was greater than that for the weld in its as-welded state. The dislocation density in the fusion zone of the joint subjected to post-heat treatment increased by only 6 × 1012 m−2 after 100 h of creep, which is significantly lower than that of the weld in its as-welded state.